COMPARATIVE ANALYSIS OF BIOMECHANICAL CHARACTERISTICS OF SWIMMING IN DIFFERENT STYLES IN STUDENTS WITH DIFFERENT LEVELS OF TRAINING - Ruzieva Mahliyo Kayumovna (Proximus Journal Publishing, 2025)
This article presents a comparative analysis of the biomechanical characteristics of swimming in different styles (crawl, breaststroke, backstroke and butterfly) in students with different levels of training (beginners and advanced swimmers). The aim of the study is to identify key differences in swimming technique that affect the speed and efficiency of movements in the water. The paper examines such parameters as stroke frequency, stroke length, attack angle, body position in the water and coordination of movements. The results can be used to develop individual training programs and improve the swimming technique of students at the university
Keywords: swimming; biomechanics; swimming styles